Your credit score, your money & what's at stake : how to improve the 3-digit number that shapes your financial future - Weston, Liz Pulliam (FT Press, 2009)
"A great credit score can help you finish rich! Liz Pulliam Weston gives solid, easy-to-understand advice about how to improve your credit fast. Read this book and prosper." David Bach, bestselling author of The Automatic Millionaire and The Automatic Millionaire Homeowner "Excellent book! Insightful, well written, and surprisingly interesting. Liz Pulliam Weston has done an outstanding job demystifying an often intimidating and frustrating topic for the benefit of all consumers." Eric Tyson, syndicated columnist and bestselling author of Personal Finance for Dummies "No one makes complex financial information easy to understand like Liz Pulliam Weston. Her straight-talk and wise advice are invaluable to anyone with a credit card or check book-and that's just about all of us." Lois P. Frankel, Ph. D., author of Nice Girls Don't Get the Corner Office and Nice Girls Don't Get Rich "In a country where consumers increasingly pay more when they have bad credit, Liz Pulliam Weston's book provides excellent tips and advice on ways to improve your credit history and raise your credit score. If you just apply one or two of her insightful suggestions, you'll save many times the cost of this book." Ilyce R. Glink, financial reporter, talk show host, and bestselling author of 100 Questions Every First-Time Home Buyer Should Ask "Your credit score can save you money or cost you money-sometimes a lot of money. Yet, most people don't even know their scores, much less know how to make them better. Liz Pulliam Weston can help you fix that. In this easy-to-understand guide you'll learn how to make sure your score helps you get the best deal on loans and insurance. You can't afford not to read it." Gerri Detweiler, consumer advocate and founder of UltimateCredit.com The #1 Best-Selling Guide to Improving Your Credit Score ... Now Thoroughly Updated for the Financial Crisis! In post-crash America, it's tough to get credit ... and even tougher to get rates and terms you can afford. That makes your credit score more important than ever before. Now, MSN Money/L.A. Times personal finance columnist Liz Pulliam Weston has updated her best-selling book on credit scores to show how you can maximize your score right now-and save yourself a fortune! Weston reveals the tough new realities of borrowing and credit scoring, and shows why they aren't going to change any time soon. She rips away the mystery surrounding credit scoring, including the FICO 08 overhaul, and tells y ...